PERAN EDUKASI LITERASI DIGITAL DALAM MENINGKATKAN KONTROL DIRI SISWA TERHADAP PENGGUNAAN GADGET SDN 10 TANJUNG LAGO - Hurriyati, Dwi; Della, Della (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This program aims to increase students’ self-control using gadgets through digital literacy education at SD Negeri 10 Tanjung Lago. Activities are carried out through the delivery of digital literacy materials, distribution of the QR Code video, implementation of geometric games, as well as providing a checklist of self-control. Based on initial observations, students are known to have not been able to manage the use of gadgets optimally and do not yet understand the limits in choosing safe and useful digital content. After participating in a series of activities, students show an increase in understanding of the use of wise gadgets, including digital ethics and safety of personal data. The results of self-control scale indicate that 15% of students are in very high categories, 30% of high categories, 35% of moderate categories, 15% of low category, and 5% of categories are very low. The findings suggest that most students are in medium to high categories, demonstrating the increased ability.